Comparison of the Sorption of Cu(II) and Pb(II) by Bleached and Activated Biochars: Insight into Complexation and Cation–π Interaction - Jing Zhao; Lin Wang; Gang Chu (Agronomy, 2023)
Attention has been paid to the application of biochar in the remediation of heavy metal contamination in soils. In this study, two modification methods, bleaching and activation, were used to enhance the biochar sorption of Cu(II) and Pb(II). Multiple techniques, including XPS, FTIR and 13C NMR, were applied to investigate the properties of bleached and activated biochars. Combined with density functional theory (DFT) calculations, structural changes in the biochars and the main mechanism of Cu(II) and Pb(II) sorption were discussed after modification. The bleached biochar without non-condensed aromatic C possessed many oxygen-containing groups due to oxidation. In contrast, activation increased the specific surface area (SSA) and removed the carboxyl groups. Both modifications had an excellent effect on sorption by high-temperature biochars, especially the bleaching treatment. The bleached and activated biochars exhibited superior Pb(II) sorption compared with Cu(II) due to the larger electron cloud configuration of Pb(II). The significantly positive correlation of the Kd values with the COOH/C=O content indicated that the oxygen-containing groups were responsible for Cu(II) and Pb(II) sorption. The DFT calculation demonstrated a higher energy for the cation–π interaction than for the complexation for Cu(II) sorption, whereas the opposite case was observed for Pb(II) sorption. The complexation and cation–π interaction were the main mechanisms of Cu(II) and Pb(II) sorption. This study provides important guidance for the application of modified biochars in the sorption of heavy metals in the environment.